Extremely black color changing film and preparation method thereof

By adding carbon nanotubes to the extremely black structure glue layer of the extremely black color change film and adopting a simplified TPU composite structure, the existing black color change film has been solved, and higher blackness retention and mechanical properties have been achieved.

CN119859479APending Publication Date: 2025-04-22江苏晶华新材料科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510150977.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-11
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The existing black color change films have problems such as different color depths, red or yellowing in color rendering effects, poor durability and complex structural processes, resulting in insufficient mechanical performance.

Method used

An extremely black color-changing film structure consisting of a first release film, an acrylic adhesive layer, an extremely black structure adhesive layer, a substrate layer, a thermal repair layer and a second release film are adopted, and carbon nanotubes are added to the extremely black structure adhesive layer to increase the blackness.

Benefits of technology

Higher blackness retention is achieved, mechanical properties and durability are improved, while simplifying structural processes, reducing costs and improving stretching effects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119859479A_ABST
    Figure CN119859479A_ABST
Patent Text Reader

Abstract

The invention discloses an extremely-black color-changing film and a preparation method thereof. The extremely-black color-changing film sequentially comprises a first release film, an acrylic acid adhesive layer, an extremely-black structural adhesive layer, a base material layer, a thermal repair layer and a second release film from bottom to top, wherein the extremely black structural adhesive layer comprises the following components in percentage by mass: 28%-32% of polyurethane resin, 8%-12% of poly-carbon resin, 3%-8% of carbon nanotubes, 4%-6% of a hyperdispersant and 48%-52% of butanone. According to the extremely-black color-changing film and the preparation method thereof, the carbon nanotubes are added into the extremely-black structural adhesive layer, and the polyurethane resin can be blended into the carbon nanotubes, so that the blackness of the color-changing film can be improved, and the black color can be kept for a longer time. Furthermore, according to the extremely-black color-changing film, an existing TPU composite structure is simplified into a single-base-material-layer structure, and the cost is lower and the stretching effect is better while the mechanical performance of the color-changing film is not changed. In addition, the acrylic acid adhesive layer improves the firmness between the layer structures of the extremely black color-changing film, and the extremely black color-changing film is not easy to separate in the construction process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of thin films, and in particular relates to an extremely black color-changing film and a preparation method thereof. Background Art

[0002] The black color-changing film for cars is a thin film material used to change the color of the car's exterior. It is usually made of materials such as polyurethane, polyvinyl chloride or polyethylene terephthalate, and has the function of protecting the original car paint and improving the appearance. The black color of the black color-changing film is usually achieved by adding carbon black, organic pigment aniline black, inorganic black or other black pigments to the substrate. These pigments can absorb most of the visible light, thus presenting a deep black effect. However, the existing black color-changing film, such as uneven dispersion of carbon black or other pigments, may cause different shades of color, affecting the overall visual effect; due to differences in grinding process and raw materials, the color development effect will be red or yellow, thereby affecting the blackness effect. In addition, some pigments are prone to chemical changes when exposed to ultraviolet rays or high temperature environments for a long time, resulting in fading or discoloration. These problems further aggravate the shortcomings of the color-changing film in terms of durability and color consistency. In addition, the existing color-changing film structure process is complex, and the multi-layer composite structure will have defects during construction. The difference in mechanical properties between the color masking film and the substrate layer will cause inconsistent synchronization values ​​during stretching, resulting in the risk of film peeling; the composite structure will affect the original mechanical properties of the substrate layer, causing a decrease in the elongation at break, making it difficult to stretch during construction.

[0003] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention and should not be regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art. Summary of the invention

[0004] The object of the present invention is to provide an extremely black color-changing film, which has a higher blackness and better mechanical properties and durability.

[0005] In order to achieve the above-mentioned purpose, a technical solution provided by a specific embodiment of the present invention is as follows: an ultra-black color-changing film, which includes, from bottom to top: a first release film, an acrylic adhesive layer, an ultra-black structural adhesive layer, a substrate layer, a thermal repair layer and a second release film; wherein the components of the ultra-black structural adhesive layer include, by mass percentage: 28%-32% polyurethane resin, 8%-12% polycarbonate resin, 3%-8% carbon nanotubes, 4%-6% hyperdispersant and 48%-52% butanone.

[0006] In one or more embodiments of the present invention, the carbon nanotubes have a fibrous structure.

[0007] In one or more embodiments of the present invention, the thickness of the ultra-black structural adhesive layer is 15 μm-20 μm.

[0008] In one or more embodiments of the present invention, the components of the thermal repair layer include, by mass percentage, 65%-68% of a polyurethane copolymer, 15%-20% of isocyanate, and 12%-15% of butyl acetate.

[0009] In one or more embodiments of the present invention, the components of the acrylic adhesive layer include, by mass percentage, 66%-70% acrylic pressure-sensitive adhesive, 14%-18% ethyl acetate, and 14-18% toluene.

[0010] In one or more embodiments of the present invention, the thickness of the acrylic adhesive layer is 20 μm-40 μm; and / or the thickness of the thermal repair layer is 6 μm-15 μm.

[0011] In one or more embodiments of the present invention, the thickness of the first release film is 75 μm-92 μm; and / or the thickness of the second release film is 36 μm-75 μm.

[0012] In one or more embodiments of the present invention, the substrate layer is a TPU substrate; the thickness of the substrate layer is 100 μm-150 μm.

[0013] The technical solution provided by another specific embodiment of the present invention is as follows: A method for preparing an extremely black color-changing film, comprising: stirring polycarbonate resin, a superdispersant and butanone evenly; adding carbon nanotubes and dispersing them evenly to obtain a dispersed slurry; adding the slurry to a sand mill and grinding it until the fineness is less than 5 μm and the blackness and gloss of the slurry remain unchanged; mixing the ground slurry with a polyurethane resin and dispersing it evenly to obtain an extremely black structural adhesive; coating the extremely black structural adhesive on the surface of a substrate layer to form an extremely black structural adhesive layer and laminating a protective release film on the extremely black structural adhesive layer to obtain a first semi-finished product; after the first semi-finished product is aged at 35°C-45°C for 24h-48h, acrylic adhesive is coated on the surface of the first release film to form an acrylic adhesive layer; the protective release film of the first semi-finished product is removed, and the extremely black structural adhesive layer is laminated with the acrylic adhesive layer to obtain a second semi-finished product; coating the substrate surface of the second semi-finished product with a thermal repair adhesive to obtain a thermal repair layer; laminating a second release film on the surface of the thermal repair layer to obtain an extremely black color-changing film.

[0014] In one or more embodiments of the present invention, the polycarbonate resin, hyperdispersant and butanone are stirred uniformly at a rotation speed of 300-600 rpm; and / or, the carbon nanotubes are dispersed at a rotation speed of 1500-2000 rpm for 30 min-60 min; and / or, the slurry and the polyurethane resin are dispersed and mixed at a rotation speed of 600-1000 rpm for 20 min-30 min.

[0015] Compared with the prior art, the ultra-black color-changing film and its preparation method of the present invention add carbon nanotubes to the ultra-black structural adhesive layer. The carbon nanotubes can be integrated into the polyurethane resin, which can improve the blackness of the color-changing film. Compared with the existing black color-changing film, the blackness is higher, and the black color can be maintained for a longer time. Furthermore, the ultra-black color-changing film simplifies the existing TPU composite structure into a single substrate layer structure, which does not change the mechanical properties of the color-changing film, has lower costs and better stretching effects. In addition, the acrylic adhesive layer improves the firmness between the layer structures of the ultra-black color-changing film, and it is not easy to separate during the construction process. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0017] Figure 1 Schematic diagram of the structure of the ultra-black color-changing film in one embodiment of the present invention.

[0018] Description of main reference numerals:

[0019] 1-first release film, 2-acrylic adhesive layer, 3-extreme black structural adhesive layer, 4-substrate layer, 5-thermal repair layer, 6-second release film. DETAILED DESCRIPTION

[0020] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0021] like Figure 1 As shown, an ultra-black color-changing film in one embodiment of the present invention includes, from bottom to top, a first release film 1, an acrylic adhesive layer 2, an ultra-black structural adhesive layer 3, a substrate layer 4, a thermal repair layer 5, and a second release film 6. Among them, the components of the ultra-black structural adhesive layer 3 include, by mass percentage: 28%-32% polyurethane resin, 8%-12% polycarbonate resin, 3%-8% carbon nanotubes, 4%-6% hyperdispersant, and 48%-52% butanone.

[0022] In the above embodiment, the ultra-black structural adhesive layer 3 of the ultra-black color-changing film of the present invention is added with carbon nanotubes, which can be integrated into the polyurethane resin, and can improve the blackness of the color-changing film. Compared with the existing black color-changing film, the blackness is higher, and the black color can be maintained for a longer time. At the same time, the acrylic adhesive layer 2, the thermal repair layer 5 and the release film are matched to obtain an ultra-black color-changing car cover. Furthermore, the ultra-black color-changing film simplifies the existing TPU composite structure into a single substrate layer 4 structure, which does not change the mechanical properties of the color-changing film, has lower costs and better stretching effects.

[0023] In one embodiment, the carbon nanotubes have a fibrous structure. In the existing black color-changing film, ordinary carbon black is a spherical carbon powder particle, which absorbs, reflects and refracts light by relying on the carbon material and surface morphology, so that the incident light that can be detected is greatly reduced, forming a certain degree of blackness. The fibrous structure of the carbon nanotubes can not only absorb, reflect and refract light by relying on the carbon's own material and surface morphology, but also form a carbon tube jungle structure in the extremely black structural adhesive layer 3, and form refraction and absorption of light through the stacking structure between the carbon tubes, and finally improve the absorption rate of light on the basis of the original carbon material and surface morphology. Finally, after the same light beam enters the carbon tube jungle, less light can escape, thereby improving the blackness of the color-changing film and achieving an extremely black effect. At the same time, the firmness of the connection between the extremely black structural adhesive layer 3 and the substrate layer 4 is also improved, and it is not easy to delaminate.

[0024] Furthermore, the thickness of the ultra-black structural adhesive layer 3 is 15 μm-20 μm. The thickness of the ultra-black structural adhesive layer 3 can ensure that it has a full shielding effect and can completely cover the original car paint color.

[0025] In one embodiment, the components of the thermal repair layer 5 include, by mass percentage, 65%-68% polyurethane copolymer, 15%-20% isocyanate, and 12%-15% butyl acetate. Further, the thickness of the thermal repair layer 5 is 6 μm-15 μm. The thermal repair layer 5 can improve the high brightness and high transparency effect of the ultra-black color-changing film, as well as the thermal repair performance and anti-fouling performance.

[0026] In one embodiment, the components of the acrylic adhesive layer 2 include, by mass percentage, 66%-70% acrylic pressure-sensitive adhesive, 14%-18% ethyl acetate, and 14-18% toluene. The thickness of the acrylic adhesive layer 2 is 20 μm-30 μm. The acrylic adhesive layer 2 can firmly adhere to the ultra-black structural adhesive layer 3, adhere well to the car paint, and is easier to construct and install.

[0027] In one embodiment, the thickness of the first release film 1 is 75 μm-92 μm. The thickness of the second release film 6 is 36 μm-75 μm. Among them, the second release film 6 can be one of a high-transmittance release film, a high-transmittance hardened film or a silicone protective film. Further, the substrate layer 4 can be a TPU substrate, which can improve the flatness and tensile strength of the color-changing film. The thickness of the substrate layer 4 is 100 μm-150 μm.

[0028] In another embodiment of the present invention, a method for preparing an ultra-black color-changing film includes steps S1-S7.

[0029] Step S1: uniformly stir polycarbonate resin, hyperdispersant and butanone; add carbon nanotubes and disperse them uniformly to obtain dispersed slurry; add the slurry into a sand mill and grind it until the fineness is less than 5 μm and the blackness and gloss of the slurry remain unchanged.

[0030] Specifically, in step S1, polycarbonate resin, hyperdispersant and butanone are uniformly stirred at a speed of 300-600 rpm by a disperser. Carbon nanotubes are added and dispersed at a speed of 1500-2000 rpm for 30 min-60 min to obtain a dispersed slurry. The slurry is added to a sand mill and ground until the fineness is less than 5 μm and the blackness and gloss of the slurry remain unchanged.

[0031] Step S2: Mix the ground slurry with the polyurethane resin and disperse them evenly to obtain an ultra-black structural adhesive.

[0032] Specifically, in step S2, the ground slurry is mixed with a polyurethane resin and dispersed at a rotation speed of 600-1000 rpm for 20 min-30 min to obtain an extremely black structural adhesive.

[0033] Step S3: coating the ultra-black structural adhesive on the surface of the substrate layer to form an ultra-black structural adhesive layer and attaching a protective release film to the ultra-black structural adhesive layer to obtain a first semi-finished product.

[0034] Specifically, in step S3, a 15 μm-20 μm ultra-black structural adhesive is directly coated on the surface of the TPU substrate layer through a slit or a scraper, and a protective release film is attached to obtain a first semi-finished product.

[0035] Step S4: After the first semi-finished product is aged at 35° C.-45° C. for 24 h-48 h, acrylic adhesive is coated on the surface of the first release film to form an acrylic adhesive layer.

[0036] Specifically, in step S4, after the first semi-finished product is aged at 35°C-45°C for 24 hours-48 hours, 20 μm-40 μm of acrylic adhesive is directly coated on the surface of the first release film through a slit or a scraper to form an acrylic adhesive layer.

[0037] Step S5: removing the protective release film of the first semi-finished product, and laminating the ultra-black structural adhesive layer with the acrylic adhesive layer to obtain a second semi-finished product.

[0038] Step S6: coating a thermal repair adhesive on the surface of the substrate of the second semi-finished product to obtain a thermal repair layer.

[0039] Specifically, in step S6, a thermal repair adhesive having a thickness of 6 μm to 15 μm is directly coated on the surface of the substrate of the second semi-finished product by a micro-concave anilox roller to obtain a thermal repair layer.

[0040] Step S7: Laminating a second release film on the surface of the thermal repair layer to obtain an extremely black color-changing film.

[0041] The present invention is further described below in conjunction with specific embodiments and comparative examples.

[0042] Example 1

[0043] The extremely black color-changing film in Example 1 includes, from bottom to top: a first release film 1, an acrylic adhesive layer 2, an extremely black structural adhesive layer 3, a substrate layer 4, a thermal repair layer 5, and a second release film 6. Among them, the first release film 1: thickness 92μm. Acrylic adhesive layer 2: thickness 30μm; components: 68% acrylic pressure-sensitive adhesive, 16% ethyl acetate and 16% toluene. Extremely black structural adhesive layer 3: thickness 18μm; components: 30% polyurethane resin, 10% polycarbonate resin, 5% carbon nanotubes, 5% hyperdispersant and 50% butanone. Substrate layer 4: thickness 130μm; TPU substrate layer. Thermal repair layer 5: thickness 10μm; components: 66% polyurethane copolymer, 20% isocyanate and 14% butyl acetate. Second release film 6: thickness 50μm, high-transmittance hardened film.

[0044] Comparative Example 1

[0045] The black color-changing film in Comparative Example 1 includes, from bottom to top, a release film, a PSA layer, a color-shielding layer, a color-changing adhesive layer, a TPU substrate layer, a repair layer, and a PET protective film. Among them, the release film has a thickness of 130 μm; the PSA layer has a thickness of 55 μm; the color-shielding layer has a thickness of 60 μm; the color-changing adhesive layer has a thickness of 30 μm; the TPU substrate layer has a thickness of 150 μm; the repair layer has a thickness of 12 μm; and the PET protective film has a thickness of 50 μm.

[0046] The color-changing films of Example 1 and Comparative Example 1 were tested, and the tests included the following contents:

[0047] Scratch repairability test; Test method: Repair non-penetrating scratches with a copper brush after heating.

[0048] Anti-fouling test; Test method: M&G Double-Jie marker / Pilot big-head pen, wipe with alcohol dust-free cloth after 3 minutes.

[0049] Elongation at break; Test method: ASTM D63810.

[0050] Chemical solvent resistance; test method: ASTM D7244, ASTM D6279 heptane, hexane, toluene, isopropanol.

[0051] Stone chip resistance; Test method: SAE J400.

[0052] QUV aging; test method: ASTM G153, ≥2000 hours.

[0053] The test results are shown in Table 1 below.

[0054] Table 1 Performance test contents and results of Example 1 and Comparative Example 1

[0055]

[0056] As can be seen from Table 1 above, the anti-fouling, stretching, blackness, anti-gravel and other properties of the ultra-black color-changing film of Example 1 are better than those of the color-changing film of Comparative Example 1, and the color is better and the stretching rate is higher. In addition, the ultra-black color-changing film of Example 1 has a higher blackness and can achieve an extremely black visual effect.

[0057] In summary, the extremely black color-changing film and its preparation method of the present invention add carbon nanotubes to the extremely black structural adhesive layer 3. The carbon nanotubes can be integrated into the polyurethane resin, which can improve the blackness of the color-changing film. Compared with the existing black color-changing film, the blackness is higher, and the black color can be maintained for a longer time. Furthermore, the extremely black color-changing film simplifies the existing TPU composite structure into a single substrate layer 4 structure, which does not change the mechanical properties of the color-changing film, while having lower costs and better stretching effects. In addition, the acrylic adhesive layer 2 improves the firmness between the layer structures of the extremely black color-changing film, and is not easy to separate during construction.

[0058] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

[0059] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. An extremely black color-changing film, characterized in that: From bottom to top, it includes: a first release film, an acrylic adhesive layer, an ultra-black structural adhesive layer, a substrate layer, a thermal repair layer, and a second release film; The components of the ultra-black structural adhesive layer include, by mass percentage, 28%-32% polyurethane resin, 8%-12% polycarbonate resin, 3%-8% carbon nanotubes, 4%-6% hyperdispersant and 48%-52% butanone.

2. The ultra-black color-changing film according to claim 1, characterized in that: The carbon nanotubes have a fiber structure.

3. The ultra-black color-changing film according to claim 1, characterized in that: The thickness of the ultra-black structural adhesive layer is 15 μm-20 μm.

4. The ultra-black color-changing film according to claim 1, characterized in that: The components of the heat repair layer include, by mass percentage, 65%-68% of a polyurethane copolymer, 15%-20% of isocyanate and 12%-15% of butyl acetate.

5. The ultra-black color-changing film according to claim 1, characterized in that: The components of the acrylic adhesive layer include, by mass percentage, 66%-70% acrylic ester pressure-sensitive adhesive, 14%-18% ethyl acetate and 14-18% toluene.

6. The ultra-black color-changing film according to claim 1, characterized in that: The thickness of the acrylic adhesive layer is 20 μm-40 μm; and / or the thickness of the thermal repair layer is 6 μm-15 μm.

7. The ultra-black color-changing film according to claim 1, characterized in that: The thickness of the first release film is 75 μm-92 μm; and / or the thickness of the second release film is 36 μm-75 μm.

8. The ultra-black color-changing film according to claim 1, characterized in that: The substrate layer is a TPU substrate; the thickness of the substrate layer is 100 μm-150 μm.

9. A method for preparing the ultra-black color-changing film according to any one of claims 1 to 8, characterized in that: include: Stir the polycarbonate resin, superdispersant and butanone evenly; Add carbon nanotubes and disperse them evenly to obtain a well-dispersed slurry; The slurry is added into a sand mill and ground until the fineness is less than 5 μm and the blackness and gloss of the slurry remain unchanged; The ground slurry is mixed with a polyurethane resin and dispersed evenly to obtain an extremely black structural adhesive; The ultra-black structural adhesive is coated on the surface of the substrate layer to form an ultra-black structural adhesive layer and a protective release film is attached to the ultra-black structural adhesive layer to obtain a first semi-finished product; After the first semi-finished product is aged at 35° C.-45° C. for 24 h-48 h, acrylic adhesive is coated on the surface of the first release film to form an acrylic adhesive layer; The protective release film of the first semi-finished product is removed, and the ultra-black structural adhesive layer is laminated with the acrylic adhesive layer to obtain a second semi-finished product; Applying a thermal repair adhesive on the surface of the substrate of the second semi-finished product to obtain a thermal repair layer; A second release film is adhered to the surface of the thermal repair layer to obtain an extremely black color-changing film.

10. The method for preparing the ultra-black color-changing film according to claim 9, characterized in that: The polycarbonate resin, superdispersant and butanone are stirred uniformly at a rotation speed of 300-600 rpm; and / or, the carbon nanotubes are dispersed at a rotation speed of 1500-2000 rpm for 30 min-60 min; and / or, the slurry and the polyurethane resin are dispersed and mixed at a rotation speed of 600-1000 rpm for 20 min-30 min.